Current therapeutic targets and multifaceted physiological impacts of caffeine - Song, Xinjie; Kirtipal, Nikhil; Lee, Sunjae; Malý, Petr; Bharadwaj, Shiv (PTR. Phytotherapy research, 2023)
Caffeine, which shares consubstantial structural similarity with purine adenosine, has been demonstrated as a nonselective adenosine receptor antagonist for eliciting most of the biological functions at physiologically relevant dosages. Accumulating evidence supports caffeine's beneficial effects against different disorders, such as total cardiovascular diseases and type 2 diabetes. Conversely, paradoxical effects are also linked to caffeine ingestion in humans including hypertension-hypotension and tachycardia-bradycardia. These observations suggest the association of caffeine action with its ingested concentration and/or concurrent interaction with preferential molecular targets to direct explicit events in the human body. Thus, a coherent analysis of the functional targets of caffeine, relevant to normal physiology, and disease pathophysiology, is required to understand the pharmacology of caffeine. This review provides a broad overview of the experimentally validated targets of caffeine, particularly those of therapeutic interest, and the impacts of caffeine on organ-specific physiology and pathophysiology. Overall, the available empirical and epidemiological evidence supports the dose-dependent functional activities of caffeine and advocates for further studies to get insights into the caffeine-induced changes under specific conditions, such as asthma, DNA repair, and cancer, in view of its therapeutic applications.
Keywords: Hypertension; diabetes mellitus 2. typu; kardiovaskulární nemoci; lidé; Diabetes Mellitus, Type 2; hypertenze; kofein; Humans; Cardiovascular Diseases; Caffeine